(untitled) - Stone, Ron D. (San Francisco, CA, 2009)
Contents: About this book. Tables, figures, and exhibits. Web site tools. Preface. Introduction. Audience. How this book Is organized. Getting the most from this resource. Key terms used throughout the book. Thinking performance in the twenty-first century. Performance is our business. Performers do have a choice. Viewing training through a different lens...
Keywords: Employees,Nhân viên; Training of,Tập huấn